Superparamagnetic Nanocomposite of Magnetite-Chitosan Using Oleic Acid as Anti Agglomeration and Glutaraldehyde as Crosslinkage Agent - Suyanta Suyanta; Sutarno Sutarno; Nuryono Nuryono; Bambang Rusdiarso; Eko Sri Kunarti; Hesti Kusumastuti; Lia Kurnia (Universitas Gadjah Mada, 2019)
In this research magnetite was synthesized by coprecipitation method, in which solution of NH4OH was added into the solution containing a mixture of Fe2+/Fe3+ (molar ratio 1:2) until pH 11 under strong ultrasonic agitation for 30 min. The black sediment of magnetite was filtered, washed and dried. The product was then modified by using oleic acid to prevent agglomeration. Chitosan was prepared by deacetilization of chitin, whereas chitin was extracted from shrimp shell. In the synthesis of nanocomposite, 0.5 g of chitosan and 1.5 g of oleic acid modified magnetite were introduced into 100 mL of 2% acetic acid solution, followed by sonication treatment for 10 min and magnetic stirring for 20 min. In order to perform the cross-linkage reaction, solution of 2% glutaraldehyde was added into the mixture at temperature of 40 °C for 3 h. The composite was collected by magnetic separation, followed by washing with distilled water and ethanol in a row. The product was dried and characterized by XRD, FTIR, TEM and VSM methods. The result showed that the composite had good crystal structure with a cubic inverse spinel structure, monodisperse and quasi sphere in shape with diameter of 20–25 nm. It had high saturation magnetization (43.4 emu/g) and superparamagnetic property.